Theologizing State Crime. (1st April 2016) - Nadera Shalhoub-Kevorkian; Yossi David; Sarah Ihmoud
Abstract : This article examines a sacralized political economy of state crime, centring Israeli assaults on the occupied Gaza Strip over the last ten years, with a particular focus on the violent attack perpetrated in 2014. Taking the 2006 election of Hamas as a point of departure, the article analyses various manifestations of violence inscribed on the people of Gaza, including killing, injuring, starving, collective punishment, military assaults and other forms of cruelty. Drawing on a settler colonial framework, the article investigates Israel's violence as sacralized state criminality embedded in a local and global political economy of racism and impunity. It argues that Israeli crimes against Gazan Palestinians must be analysed as political technologies of counterinsurgent governmentality embedded in a structure of settler colonial dispossession initiated during the 1948 Nakba.